Swobody cząstkowe — próba klasyfikacji - Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Partial freedoms, reflecting different aspects of the freedom of economic activity, can be divid-ed into three groups. Inherent partial freedoms concern the necessary elements of the freedom ofeconomic activity; they define its body of content. Related partial freedoms refer to activities undertaken not only in connection with economic activity, but also in other spheres of human activity. Structural partial freedoms entitle entrepreneurs to use legal structures designed to improve the legal infrastructure for conducting economic activity. The term “limitations upon the freedom of economic activity,” contained in Art. 22 of the Constitution of the Republic of Poland, should only be used to refer to the limitations of inherent partial freedoms, relating in a specific way to the sphere of economic activity.
Keywords: freedom of economic activity; economic activity; partial freedoms; limitations upon the freedom of economic activity